Synthesis of Bioethanol from Cocoa Pod Husk Using Zymomonas Mobilis - Mu'tasim Billah; Tikat Deri Agratiyan; Dhining Ayu; Nove Kartika Erliyanti; Erwan Adi Saputro; Rachmad Ramadhan Yogaswara (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Nowadays, energy issue is one of the interesting discussions among the researchers and energy stakeholders. This is due to the reducing of the main source of world energy which consists mostly of non-renewable energy derived from fossils of living things millions of years ago. Alternatively, there are some alternative energy that promising in the future such as bioethanol from plant or fruits. For that reasons, the aim of this research is to make bioethanol from the peel of cocoa fruit. Cocoa pod husk can be used as source of bioethanol through a fermentation process with the help of bacteria. This study will examine the ethanol content in fermented cocoa pod husks. The fermentation time was 0 days, 2 days, 4 days, 6 days, 8 days. The Zymomonas mobilis bacteria is used in the fermentation process and their percentage is 8%v/v, 10%v/v, 12%v/v, 14%v/v, 16%v/v.In the process of fermentation of cocoa pod husk with Zymomonas mobilis inoculum on the 3rd day to 9thshowed an increase. On the eleventh day in all conditions the addition of a starter was decreased. The best condition when fermentation takes place on the 8th day with a starter dose of 14% and obtained an alcohol content of 10.62%.The results of this study indicate that the addition of Zymomonas mobilis starter and fermentation time affect the levels of bioethanol produced. The addition of a starter as much as 14% and the fermentation time for 8 days are the best condition in this study.